Egungun Tradition in Trado-Modern Society in South-Western Nigeria - Aremu, P. S. O.; Olanipekun, Biodun Banjo. O Yaya (Mediterranean Journal of Social Sciences, 2012)
Series of Authors have expressed their notions on Egungun tradition where it is still being practiced. The presentsituation calls for a review and re-assessment of the turn-around of its efficacy as it involves other believers (Christians andMuslims). Generally, people of the world are religious in nature, because of this simple fact, the creator-God, referred to asOlodumare among the Yoruba, is usually called upon in both the emergencies of life, day-to-day blessings, invocations, andsalutations. People attach themselves to one deity or the other for their survival in this hostile world. Mbiti (1969) states thatAfricans are notoriously religious and that the whole organization of the society is maintained by the spiritual forces that pevadesit. In support of this submission Parrinder (1954) also is of the opinion that the whole of existence is a religious phenomenon.